Progress in Avalanche Photodiodes for Laser Ranging - Zhenxing Liu; Ning An; Xingwei Han; Natalia Edith Nuñez; Liang Jin; Chengzhi Liu (Sensors)
Laser ranging is a high-precision geodetic technique that plays an indispensable role in the field of geodynamics. Avalanche photodiodes (APDs) offer a series of advantages over other photodetector technologies, including photomultiplier tubes (PMTs) and superconducting single-photon detectors (SNSPDs). These advantages include high sensitivity, small size, high integration, and low power consumption, which have contributed to the widespread use of APDs in laser ranging applications. This paper analyses the key role of APDs in enhancing the accuracy and stability of laser ranging through the examination of application examples, including Si-APD and InGaAs/InP APD. Finally, based on the technological needs of laser ranging, the future development directions of APDs are envisioned, aiming to provide a reference for the research of photodetectors in high-precision and high-frequency laser ranging applications.